Konsep Organisasi Pendidikan dalam Pemberdayaan Sekolah - Fitriyani Fitriyani (El-Ghiroh : Jurnal Studi Keislaman, 2019)
Good organization must be based on a concept that has been created based on theories that are in accordance with the objectives of the organization. as well as educational organizations, namely schools. Concepts in educational organizations are structured with the aim of empowering schools for the better. this is also encouraged by leaders or principals who have or understand the concept of good education, which is based on education and knowledge development. And this is rarely sought by the principal as a manager in an educational organization.